Implementasi Sistem Logistik Pengadaan Barang/Jasa Pada BRI Kc. Mataram - Septia Zarniwati; Nurabiah; Herlina Pusparini (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to examine the implementation of the logistics system for the procurement of goods and services at the BRI Mataram Branch Office (BRI KC Mataram). This research employs a qualitative descriptive approach through a case study conducted at BRI KC Mataram. The author was directly involved in several stages of the logistics process, including needs planning, procurement requests, supplier selection, distribution, and the receipt of goods and services. The procurement system used by BRI is digitally integrated via an internal platform that supports transparency, efficiency, and accountability at every stage of the process. The implementation of the procurement logistics system at BRI KC Mataram demonstrates adherence to good governance principles, including time efficiency, competitive supplier selection, and strict budget control. Based on observations and participation during the internship period, it can be concluded that the procurement logistics system at BRI KC Mataram has been implemented effectively and in accordance with the applicable Standard Operating Procedures (SOPs). The proposed recommendations include enhancing vendor monitoring and optimizing internal training for operational staff on the use of the digital procurement system.